The Effect of Bevacizumab and Curcumin towards the Process of Corneal Epithelization After Alkaline Trauma on Wistar Rat’s Cornea - Sri Inakawati (Majalah Oftalmologi Indonesia, 2016)
Background: The purpose of this study is to know the difference between the effect of bevacizumaband curcumin as an antiangiogenesis towards the process of corneal epithelization on alkaline traumaon Wistar rat’s cornea.Methods: Experimental research with post test only control design using 28 Wistar rats pure strain gotNaOH 1 M exposure with the diameter 1 mm in the central of cornea. Random sampling was dividedinto 4 groups which each group got bevacizumab 25 mg/ml, balanced salt solution (BSS), curcumin 80μmol/l and dimethyl-sulfoxide (DMSO) 0.1% eye drops treatment for seven days, and the examinedthe process of epithelization of the cornea and the expression of vascular endothelial growth factor(VEGF) in the corneal epithelium.Results: We found very significant differences in corneal epithelization process after giving topicalbevacizumab 25 mg/ml and curcumin 80 μmol/l on the alkaline trauma in the cornea of Wistar rats,where corneal epithelization on Curcumin is better than bevacizumab (p=0.027). An expression ofVEGF in corneal epithelium between the alkaline trauma on the pure strain of Wistar rat significantlyis different with p=0.00, which the expression on the provision of VEGF bevacizumab is lighter thanthe provision of curcumin.Conclusion: Giving curcumin on the alkaline trauma of Wistar rat resulted in better epithelization.The expression of VEGF in topical bevacizumab were lighter than the provision of curcumin. Keywords: bevacizumab, curcumin, BSS, DMSO, NaOH, corneal epithelization